Auto-Craniotomy in Head Injury: A Rare Case Report - Acharya, Abhijit; Mahapatra, A. K.; Panigrahi, Souvagya; Deo, Rama Chandra (Indian Journal of Neurotrauma, 2025)
Skull fractures are the well-known entity in patients with road traffic accidents (RTA) and falls from height. Skull fractures can be classified in view of site (basal or calvarial), pattern (linear, depressed, and diastasis), or type (simple or compound). Most patients commonly present with linear skull fractures. Elevated skull fractures (ESF) are a rare entity of skull fractures present in a few cases with fewer publications in literature. Most skull fractures occur due to a force acting in a perpendicular direction; however, elevated fractures occur due to force acting in a tangential direction on the calvarium. We present to you a 42-year-old male patient with a known case of psychiatric illness presented with a history of a fall from height followed by altered sensorium. On clinical evaluation and imaging, the patient has a large “skull cap” pattern of elevated calvarial fracture with a large extradural hematoma, subdural hematoma, diffuse cortical subarachnoid haemorrhage, and fronto-parietal contusion. He was operated on in emergency with a “S”-shaped incision with the removal of the fractured calvarial segment with lax duroplasty. In the post-operative period, the patient underwent tracheostomy and improved partially. He is on follow-up at present.
Keywords: skull cap fracture; head trauma; traumatic brain injuries; auto craniotomy